Buprenorphine implants in medical treatment of opioid addiction. Issue 8 (3rd August 2017) - Chavoustie, Steven; Frost, Michael; Snyder, Ole; Owen, Joel; Darwish, Mona; Dammerman, Ryan; Sanjurjo, Victoria
ABSTRACT: Introduction : Opioid use disorder is a chronic, relapsing disease that encompasses use of both prescription opioids and heroin and is associated with a high annual rate of overdose deaths. Medical treatment has proven more successful than placebo treatment or psychosocial intervention, and the partial µ-opioid receptor agonist and κ-opioid receptor antagonist buprenorphine is similar in efficacy to methadone while offering lower risk of respiratory depression. However, frequent dosing requirements and potential for misuse and drug diversion contribute to significant complications with treatment adherence for available formulations. Areas covered : This review describes the development of and preliminary data from clinical trials of an implantable buprenorphine formulation. Efficacy and safety data from comparative studies with other administrations of buprenorphine, including tablets and sublingual film, will be described. Key premises of the Risk Evaluation and Mitigation Strategy program for safely administering buprenorphine implants, which all prescribing physicians must complete, are also discussed. Expert commentary : Long-acting implantable drug formulations that offer consistent drug delivery and lower risk of misuse, diversion, or accidental pediatric exposure over traditional formulations represent a promising development for the effective treatment of opioid use disorder.